Obfuscatable aggregatable signcryption scheme with PadSteg for unattended devices in IoT systems - Uwadiegwu, Inyama Victor (2019)
Obfuscatable Aggregatable Signcryption (OASC) is the combination of cryptography technique such as digital signature with data encryption and obfuscation to protect data in the IoT system. It is efficacious to protecting the confidentiality and integrity of communication in Internet of Things (IoT) system. Wireless Sensor Network (WSN) is now an inevitable component of the Internet of Things (IoT), this integration creates new security challenges that exist between the sensor nodes and to the sink or internet host. For instance, when a sensor node is transmitting data from one node to another there is inadequate security mechanism which an intruder or a man in the middle (MITM) attack can capture the ciphertext to get secrete keys in other to decrypt the ciphertext. The aggregatable signcryption that enables special signcryption ciphertexts intended for the same destination be assembled in a compressed single ciphertext while maintaining the same security standards in the system. The procedure is then obfuscated aimed at making information more difficult to be understood by human being for the purpose of security and privacy of the program/information while commonly maintaining its computational functions. Unfortunately, most of these devices are left unattended or in remote places which gives an attacker a comfortable scenario to not only intercept transmission within range but also have physical access to components without been caught. This leaves some vulnerability during communication. In other to achieve the security enhancement, efficiency and reduce communication overheads by using small security parameter and the effect of such a security complexity trade-off. Motivated by this issue, we propose Signcryption Obfuscatable and Steganography-PadSteg (SOS) algorithm as a solution. Having Signcryption (digital signature and encryption) at each node is the baseline of security but the caveat is that the computational power of these components means both mechanisms will not be of highest security level hence the need to protect the information as it travels for a final process of obfuscation. This is achieved by employing a type of Network Steganography known as PadSteg and hiding these data in padded segments of choice protocols (ARP/TCP/UDP/ICMP) which will not be visible to an observer. At the end of this thesis, we achieved the result to solve the security issues mention above and to enhance the security in IoT system. The simulation result on different nodes showed that the proposed algorithm on Signcryption Obfuscatable and Steganography-PadSteg (SOS) performs 25% reasonably well as expected. The scheme will be useful in a various scenario of IoT environment where data is sent from unattended nodes to the destination known as a sink or receiver.